The current macroeconomic crisis - Bill Gibson (University of Massachusetts, Department of Economics, 2008)
Professor Crotty once casually observed that in his view economics could not be properly thought of as a science. This paper investigates the implications of this view in light of the question of how the scientific method has recently contributed to the evolution of economic practice. It is argue that agent-based models might provide a platform for an integration of recent micro and macroeconomic theories.
Keywords: 330